2018
DOI: 10.17159/sajs.2018/4451
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and other drug use among women seeking substance abuse treatment in the Western Cape, South Africa

Abstract: Despite a high prevalence of alcohol and other drug use (AOD) in South Africa, little is known about AOD use among women, including those in treatment centres, and changes in use over time. This knowledge is important for the development of gender-sensitive interventions for the prevention and treatment of AOD problems. We aimed to describe changes in patterns of AOD use among women who accessed specialist AOD treatment centres in the Western Cape Province of South Africa. Data were collected from 51 specialis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 21 publications
4
56
3
2
Order By: Relevance
“…type stimulants [2,3] . Methamphetamine use has been associated with psychotic symptoms and admission to inpatient psychiatric facilities [4,5] .…”
mentioning
confidence: 99%
“…type stimulants [2,3] . Methamphetamine use has been associated with psychotic symptoms and admission to inpatient psychiatric facilities [4,5] .…”
mentioning
confidence: 99%
“…The number of methamphetamine users in the Western Cape has increased rapidly since 2000 (18, 19), and a recent community-based study of methamphetamine users found a very high prevalence of dependence on the drug (20). Among persons entering substance abuse treatment, the proportion reporting methamphetamine as their primary drug increased from 0.3% in 2002 to 42.3% in 2006; since then, methamphetamine has accounted for 40-50% of admissions (21, 22). Methamphetamine use in Cape Town is most common among “Coloured” persons, but the prevalence appears to be increasing among Black Africans (these terms originate from the apartheid era and are still used as demographic markers referring to people of mixed versus African ancestry, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Methamphetamine use in Cape Town is most common among “Coloured” persons, but the prevalence appears to be increasing among Black Africans (these terms originate from the apartheid era and are still used as demographic markers referring to people of mixed versus African ancestry, respectively). Among persons entering substance abuse treatment for methamphetamine in 2012, 84% were Coloured and 8% were Black (23). By 2014, this proportion had shifted to 70% Coloured and 17% Black (24).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations